2019
DOI: 10.3389/fpls.2019.00123
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Flavonoids and Carotenoids and Their Contributions to Various Colors of Rose Cultivars (Rosa spp.)

Abstract: Rose is one of the most valuable ornamental crops worldwide. In this study, the composition of hydrophilic and lipophilic pigments in petals of six rose cultivars at seven developing stages was investigated using high performance liquid chromatography and mass spectrometry. Four anthocyanins, 20 flavonols, and 10 carotenoids were detected in petals of tested cultivars. Major individual anthocyanin, flavonol, and carotenoid were cyanidin/pelargonidin 3,5-diglucoside, kaempferol 3- O -rham… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 89 publications
(46 citation statements)
references
References 47 publications
(75 reference statements)
3
38
0
Order By: Relevance
“…Yamagishi et al [ 26 ] reported that Lilium ‘Montreux’, which has pink tepals, revealed decreasing patterns of total carotenoid contents in the four stages of tepals; however, the other cultivar, Lilium ‘Connecticut King’, which has yellow tepals, showed increasing patterns of carotenoid contents, which is consistent with our study. Among six rose cultivars ( Rosa ‘Yellow Island’, Rosa ‘Chacok’, Rosa ‘Garden City’, Rosa ‘Yunzheng Xiawei’, Rosa ‘Wangri qinghuai’, and Rosa ‘Pink Fan’), the greatest levels of carotenoids, flavonols, and anthocyanins increased and then decreased according to the seven different developmental stages [ 27 ]. Phenolic acids, including gallic acid, caffeic acid, and p -coumaric acid, as well as anthocyanins, decreased according to the flower stages of rose cultivar ‘KORcrisett’ [ 28 ], and a decreasing pattern of total phenolic content was observed in the petals of eight cultivars of Rosa × hybrida (‘NOAschnee’, ‘KOReb’, ‘Sea Foam’, ‘The Fairy’, ‘KORverlandus’, ‘POUleas’, ‘MORedfar’, and ‘Gärtnerfreude’) during the four flower developmental stages [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…Yamagishi et al [ 26 ] reported that Lilium ‘Montreux’, which has pink tepals, revealed decreasing patterns of total carotenoid contents in the four stages of tepals; however, the other cultivar, Lilium ‘Connecticut King’, which has yellow tepals, showed increasing patterns of carotenoid contents, which is consistent with our study. Among six rose cultivars ( Rosa ‘Yellow Island’, Rosa ‘Chacok’, Rosa ‘Garden City’, Rosa ‘Yunzheng Xiawei’, Rosa ‘Wangri qinghuai’, and Rosa ‘Pink Fan’), the greatest levels of carotenoids, flavonols, and anthocyanins increased and then decreased according to the seven different developmental stages [ 27 ]. Phenolic acids, including gallic acid, caffeic acid, and p -coumaric acid, as well as anthocyanins, decreased according to the flower stages of rose cultivar ‘KORcrisett’ [ 28 ], and a decreasing pattern of total phenolic content was observed in the petals of eight cultivars of Rosa × hybrida (‘NOAschnee’, ‘KOReb’, ‘Sea Foam’, ‘The Fairy’, ‘KORverlandus’, ‘POUleas’, ‘MORedfar’, and ‘Gärtnerfreude’) during the four flower developmental stages [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…The dried leaves of A. bilimbi tend yellow colour. It represents the presence of flavonoid compounds, where flavonoid compounds are active compounds that have yellow, orange to orange pigments (Wan et al, 2019). Based on the colour analysis that showed the yellow dark of A. bilimbi extract, this study suggested to use A. bilimbi leaves as food dyes and herbal tea.…”
Section: Physicochemical Properties and Mineral Contents Of A Bilimbmentioning
confidence: 89%
“…By contrast, even flowers of the same color exhibited distinct carotenoid profiles depending on the species and variety. In yellow tomato flowers, neoxanthin and violaxanthin comprise the two major carotenoids, whereas 9-cis-violaxanthin is the predominant component in yellow rose flowers (Ariizumi et al, 2014;Wan et al, 2019). Zhang et al (2015) reported that the carotenoids present in yellow petals of B. napus are composed of approximately 90% violaxanthins.…”
Section: Discussionmentioning
confidence: 99%